Chitosan/fucoidan multilayer nanocapsules as a vehicle for controlled release of bioactive compounds - Pinheiro, A. C. (2015)
Abstract Hollow multilayer nanocapsules were successfully prepared through layer-by-layer assembly of two bioactive polysaccharides, chitosan and fucoidan. The stepwise adsorption of 10 chitosan/fucoidan layers and the consequent formation of a multilayer film on polystyrene nanoparticles (used as templates) were followed through ζ-potential measurement and the removal of the polystyrene core was confirmed by FTIR analysis. The chitosan/fucoidan nanocapsules morphology and size were evaluated by SEM and TEM, that showed that after the core removal, the nanocapsules maintained their spherical shape and a decrease of size occurred. A cationic bioactive compound, poly-L-lysine (PLL), was chosen to evaluate the loading and release behaviour of the nanocapsules. The chitosan/fucoidan nanocapsules showed a good capacity for the encapsulation and loading of PLL, which shows to be influenced by the initial PLL concentration and the method of encapsulation used. The results of fitting the linear superimposition model to the experimental data of PLL release suggest an anomalous behaviour, with one main polymer relaxation. The PLL release was found to be pH-dependent: at pH 2 relaxation is the governing phenomenon and at pH 7 Fick's diffusion is the main mechanism of PLL release. Chitosan/fucoidan nanocapsules is a promising delivery system for water soluble bioactive compounds, such as PLL, showing a great potential of application in food and pharmaceutical industries